A GENUINE BLEND OF STATECRAFTS: China's Smart Power Strategy in the MENA Region. (September 2022) - Altin, Hasan
Power transition in the international order and the position of China in this order have triggered ramifications in China's foreign policy strategy toward the Middle East and North Africa (MENA) region. Its foreign policy approach has evolved from strict non-intervention to an assertive policy at the international level and constructive engagement at the regional level. China has simultaneously been applying both soft and hard power to protect its national interests in MENA. This study aims to assess China's four-pillar MENA policy from the perspective of its smart power strategy by examining its hard power means and soft power tools .